2018
DOI: 10.22260/isarc2018/0170
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Virtual Reality Visualizations on Heavy Mobile Crane Planning for Modular Construction

Abstract: Many kinds of industrial projects involve the use of prefabricated modules built offsite, and installation on-site using mobile cranes. Due to their costly operation and safety concerns, utilization of such heavy lift mobile cranes requires a precise heavy lift planning. Traditional heavy lift path planning methods on congested industrial job sites are ineffective, time-consuming and non-precise in many cases, whereas computer-based simulation models and visualization can be a substantial improving tool. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The results indicate that this tool can improve the operator's confidence and safety. Researchers developed a VR platform that can simulate the heavy mobile crane lift in modular construction [60]. This platform enables the lift crew and engineers to simulate the lift in an IVE and evaluate different options in real-time.…”
Section: Ar/vr In Aecmentioning
confidence: 99%
“…The results indicate that this tool can improve the operator's confidence and safety. Researchers developed a VR platform that can simulate the heavy mobile crane lift in modular construction [60]. This platform enables the lift crew and engineers to simulate the lift in an IVE and evaluate different options in real-time.…”
Section: Ar/vr In Aecmentioning
confidence: 99%
“…Creating a Virtual Reality simulator of heavy mobile crane operations that can be employed for user training by doing the lifting process in the virtual world before the real project [12]; developing a framework to create training simulators of heavy construction machinery to improve productivity, safety, and quality perspective [9]; developing VR and MR learning and education program to evaluate the power of VR and MR to facilitate the knowledge acquisition [39]; developing a VR safety training program that is related to electrical hazards in the US construction environment [40]; and utilizing VR system to experiment the user's social behavior in the hazardous situation [41] Project planning Using a VR application in the construction job site for site layout planning, evaluation of construction site logistics planning, and collision detection [42], and utilizing VR and AR as a prototype tool to do the site planning, support construction layout, and rationalization of the logistics for increasing the productivity and decreasing the operating cost [43] Augmented VR Using a mobile AR to support monitoring and documentation of construction site improvement to visualize progress information [44]. Utilizing AR in the case of problem saving, design alternatives and decision-making through a design review activity [45].…”
Section: Section Applicationmentioning
confidence: 99%
“…Some construction companies use AR to identify hazards and falling of their workers in their workplace [10,11]. Based on the research of [10][11][12][13], there is significant potential for the wider adoption of VR and AR devices in the construction industry. VR may be helpful for training construction workers at low cost, with fewer safety risks, and faster methods in a virtual environment [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many studies have shown, VR can improve spatial perception (Paes et al 2017) and improving spatial perception along with one to one scale level of VR can help technicians to detect the discrepancies faster and more efficient. Furthermore, VR can improve communication between different parties (Balali et al 2018), improve safety (State and State 2017), and provide effective training programs (Kayhani et al 2019). In addition, combining VR with hand motion tracking technologies such as Leap Motion can provide a realistic first-person situation where the user can interact, move, and rotate the objects using their hands (Hilfert and König 2016).…”
Section: Introductionmentioning
confidence: 99%